An intervention to optimise coach-created motivational climates and reduce athlete willingness to dope (CoachMADE): a three-country cluster randomised controlled trial. Issue 4 (11th September 2020) - Ntoumanis, Nikos; Quested, Eleanor; Patterson, Laurie; Kaffe, Stella; Backhouse, Susan H; Pavlidis, George; Whitaker, Lisa; Barkoukis, Vassilis; Smith, Brendan J; Staff, Helen R; Gucciardi, Daniel F
Abstract : Objectives: Coach-centred antidoping education is scarce. We tested the efficacy of a motivationally informed antidoping intervention for coaches, with their athletes' willingness to dope as the primary outcome. Methods: We delivered a cluster randomised controlled trial in Australia, the UK and Greece. This study was a parallel group, two-condition, superiority trial. Participants were 130 coaches and 919 athletes. Coaches in the intervention group attended two workshops and received supplementary information to support them in adopting a motivationally supportive communication style when discussing doping-related issues with their athletes. Coaches in the control condition attended a standard antidoping workshop that provided up-to-date information on antidoping issues yet excluded any motivation-related content. Assessments of willingness to dope (primary outcome) and other secondary outcomes were taken at baseline, postintervention (3 months) and at a 2-month follow up. Results: Compared with athletes in the control group, athletes in the intervention group reported greater reductions in willingness to take prohibited substances (effect size g=0.17) and psychological need frustration (g=0.23) at postintervention, and greater increases in antidoping knowledge (g=0.27) at follow-up. Coaches in the intervention group reported at postintervention greater increases in efficacy to create an antidoping culture (g=0.40) and in perceived effectiveness of need supporting behaviours (g=0.45) to deal with doping-related situations. They also reported greater decreases in doping attitudes (g=0.24) and perceived effectiveness of need thwarting behaviours (g=0.35). Conclusions: Antidoping education programmes should consider incorporating principles of motivation, as these could be beneficial to coaches and their athletes. We offer suggestions to strengthen these programmes, as most of the effects we observed were not sustained at follow-up. Trial registration number: This trial has been registered with the Australian New Zealand Clinical Trials Registry (https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=371465&isReview=true ).